A power-distribution-ratio real-time tunable power divider based on active plasmonic waveguide - Shun Lei; Biao Zhu; Mingzhe Hu; Lepeng Zhang; Chaobiao Zhou; Hongyin Yang; Jie Xu; Rong Su; Haochi Zhang (Scientific Reports)
Abstract In this paper, a dynamic controllable unequal power divider based on spoof plasmonic waveguide loaded with varactors is proposed, which is mainly composed of a double-sided corrugated metal strip coupled with two branch single-sided plasmonic strips. In order to allocate electromagnetic (EM) energy flexibly, varactors are loaded in the coupling gap to adjust the coupling coefficient. Both simulation and measurement results prove that the proposed plasmonic power divider can adjust and control the power distribution ratio in a real time manner in the range of 4.5–6 GHz frequency band with a maximum power allocation ratio of 2.7 at 5.77 GHz. The plasmonic power divider possesses good frequency selectivity, especially the dynamical response to varactor voltages. Therefore, it can be expected that the proposed unequal power divider will stimulate further research on spoof surface plasmon polaritons (SSPPs) for the design of new planar active microwave components, circuits and systems in the future.